2016
DOI: 10.1080/15384047.2016.1235661
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4500 is epigenetically downregulated in colorectal cancer and functions as a novel tumor suppressor by regulating HMGA2

Abstract: This study aimed to understand the exact function and potential mechanism of miR-4500 in colorectal cancer (CRC). In this study, the expression of miR-4500 was decreased in both CRC cells and tissues, and downregulated miR-4500 indicated advanced tumor stage and poor survival. By bisulfite sequencing analysis, we found that the CpG island in the promoter region of miR-4500 was hypermethylated in CRC cells and tissues compared with normal control cells and non-tumor tissues, respectively. Functionally, gain-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…These studies were mainly conducted in East Asia, Europe, and the United States of America. The cancer types studied were: gastric cancer (GC) [ 16 18 ], breast cancer (BC) [ 10 , 19 ], hepatocellular carcinoma (HCC) [ 11 , 13 ], colorectal cancer (CRC) [ 14 , 20 , 21 ], ovarian cancer (OC) [ 22 , 23 ], nasopharyngeal carcinoma (NPC) [ 24 , 25 ], esophageal carcinoma (EC) [ 26 , 27 ], head and neck squamous cell carcinoma (HNSCC) [ 28 30 ], clear cell renal cell carcinoma [ 12 ], intrahepatic cholangiocarcinoma [ 31 ], glioblastoma [ 32 ], gallbladder adenocarcinoma [ 33 ], melanoma [ 34 ], non-small-cell lung cancer [ 35 ], and bladder cancer [ 36 ]. HMGA2 was detected using immunohistochemistry (IHC) (24 studies), reverse transcription-polymerase chain reaction (RT-PCR) (2 studies), or quantitative real-time polymerase chain reaction (qRT-PCR) (3 studies).…”
Section: Resultsmentioning
confidence: 99%
“…These studies were mainly conducted in East Asia, Europe, and the United States of America. The cancer types studied were: gastric cancer (GC) [ 16 18 ], breast cancer (BC) [ 10 , 19 ], hepatocellular carcinoma (HCC) [ 11 , 13 ], colorectal cancer (CRC) [ 14 , 20 , 21 ], ovarian cancer (OC) [ 22 , 23 ], nasopharyngeal carcinoma (NPC) [ 24 , 25 ], esophageal carcinoma (EC) [ 26 , 27 ], head and neck squamous cell carcinoma (HNSCC) [ 28 30 ], clear cell renal cell carcinoma [ 12 ], intrahepatic cholangiocarcinoma [ 31 ], glioblastoma [ 32 ], gallbladder adenocarcinoma [ 33 ], melanoma [ 34 ], non-small-cell lung cancer [ 35 ], and bladder cancer [ 36 ]. HMGA2 was detected using immunohistochemistry (IHC) (24 studies), reverse transcription-polymerase chain reaction (RT-PCR) (2 studies), or quantitative real-time polymerase chain reaction (qRT-PCR) (3 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that HMGA2 is overexpressed in cancer cells and promotes angiogenesis . And miR‐4500, miR‐98‐5p and miR‐485‐5p have been reported to directly target the 3′‐UTR of HMGA2 in other cell‐type studies. These cases profile the bright prospects of hsa_circ_0002579, which acts as a ceRNA molecule interacting with miRNAs to regulate the proliferation of HASMCs by targeting HMGA2.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, miR-4500 was identified as a target of BZW2. Previous studies have demonstrated the roles of miR-4500 in the occurrence and development of various cancers including hepatoma, non-small cell lung cancer (NSCLC) and colorectal cancer [22][23][24][25]. For instance, Zhang and colleagues have demonstrated the low expressions of miR-4500 associated with cancer cell proliferation in NSCLC [22].…”
Section: Discussionmentioning
confidence: 99%